Dempster Shafer for Computer Malfunction Detection System - Ginting, Lisa Melvi; Sari, Ressy Dwitias; Lubis, Azmi Rizki; Harahap, Vivi Ramayanti; Mendoza, Mhd. Dominique; Hutahaean, Harvei Desmon (Bahasa Indonesia, 2023)
Computers have helped humans work better and help in solving problems. Computers continued to evolve and innovation continued, starting with the first very large computers and evolving into the modern, commonly used desktops. When there is a problem with the computer device, such as damage to the computer components. Most people immediately take it to a computer repair service technician. An expert system is a component of artificial intelligence. In order for computers to solve issues in the same way that professionals do, expert systems attempt to incorporate human knowledge into computers. A single technique inside the expert system is the Dempster Shafer technique. The Dempster-Shafer technique is a mathematically based approach that incorporates uncertainty and features traits of expert thought. The research was carried out by detecting computer damage based on the sound that comes out when the BIOS performs a POST (Power On Self-Test) using the Dempster-Shafer method. Users can determine the kind of damage their machine has sustained without having to visit a computer repair service provider directly by using the Dempster Shafer approach.